REDUCING SEED INTENSITY BY OPTIMIZING THE TECHNOLOGICAL PARAMETERS OF THE LINTER MACHINE (INTERNATIONAL CONFERENCE ON ADVANCE SCIENCE AND TECHNOLOGY, 2025)
This article investigates the fuzziness level of seed cotton exiting the linter machine and explores possibilities for its reduction. The research proposes a technology that independently controls the rotational speeds of the saw cylinder and the beater components using variable frequency drives (VFDs). Through this approach, the linear speed of each working unit is synchronized, and an optimal speed ratio between them is maintained. The results indicate that the proposed control technology significantly reduces seed fuzziness and enhances seed quality.